The shepherd of Hermas : some aspects of its composition and transmission - Kirkland, Alastair (Classical Studies, 2016)
The authorship and time of origin of the Shepherd have not been subjected to the same rigorous enquiry as the First Epistle of Clement and the Epistles of Ignatius. The reason for this is probably that the Shepherd has had little to contribute to contemporary polemics in the way that the other two Apostolic Fathers did. The method followed in this study is the reconstruction, where possible, of the contents of each codex of which we have fragments or quotations, and the comparison of the contents of these codices. Where the content of the original codex appears to have been only a part of the Shepherd, calculations based on the traditional three sections - Visions, Mandates and Similitudes - have been used. Where these have not sufficed, manuscript notations have been called into play. The results indicate that there are a number of lines of cleavage within the Shepherd where ancient codices began or ended their selection of material. These lines of cleavage, it is hypothesised, must have originated in the process of composition of the Shepherd. Yet at the same time there was in the ancient codices a perception of the various parts of the Shepherd as a unity. The oldest codex known to us contains the Shepherd in its entirety. Once the lines of cleavage have been established by means of the reconstructed codices and the manuscript notations, a study of internal inconsistences of the sort traditional in "Quellenkritik" or "Literary Criticism" is undertaken, and a chronological schema of the different strands which make up the Shepherd is offered. It is suggested that the core (Viss. I to IV, Mandd. I to XIIa, Simm. I singular parts only, II to VIII) came from one hand, probably towards the end of the first century. This core underwent four subsequent editorial reworkings which produced the text known to us today by the end of the second century.